SISTEM REKOMENDASI KEBUTUHAN NUTRISI MAKANAN PENDAMPING AIR SUSU IBU (MPASI) MENGGUNAKAN METODE FUZZY TAHANI SEBAGAI UPAYA PENCEGAHAN STUNTING - Diah A.P, Zahwa; Musaruddin, Mustarum; Adi Saputra, Rizal (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2024)
Stunting is a significant child health issue in Indonesia, where children experience impaired growth, resulting in weight and height below their age average. In 2022, the World Health Organization (WHO) and the Indonesian Nutrition Status Survey (SSGI) reported a stunting prevalence of 21.6%, exceeding the WHO target of 20%. Stunting is caused by chronic malnutrition from pregnancy through the first thousand days of life, a crucial period for brain and cognitive development. Proper complementary feeding (MPASI) after 6 months is essential to meet infants' nutritional needs and prevent developmental delays in children under two. This study aims to develop a mobile web-based system that recommends MPASI according to infants' nutritional needs using the Fuzzy Tahani method. This method was chosen for its ability to handle uncertainty and provide personalized solutions. The developed system achieved 94.5% accuracy, with a precision of 33.1%, recall of 27.4%, and specificity of 85.9%. The system met the research objectives despite lower precision and recall due to imbalanced training data. User Acceptance Testing (UAT) results indicated that 77.73% of users strongly agreed with the system, while 1.86% disagreed. This system is expected to assist in preventing stunting by providing more accurate MPASI recommendations tailored to each infant's needs.